Predicting the age and weight at puberty of Ongole Grade cattle using nonlinear mathematical model in Kebumen Farmer Association - Maharani, D.; Amrullah, A. H. K.; Widayati, D. T.; Sumadi, S.; Fathoni, A.; Khusnudin, M. (Journal of the Indonesian Tropical Animal Agriculture, 2017)
This research is aimed to evaluate the nonlinear mathematical model in predicting the age and weight of Kebumen Ongole Grade (PO) cattle at puberty. The data used in this research was weight recordings of (768) PO cattle, ranging from calf (< 1 month) to adult (60 months), collected by Kebumen PO cattle Breeder Association (ASPOKEB) from 2013 to 2015. These cattle were reared by a group of farmers located in six sub-districts: Mirit, Lembu Purwo, Ambal, Puring, Petanahan, and Klirong in Kebumen district, Jawa Tengah Province. Brody, Bertalanfy, Logistic and Gompertz mathematical models were used to analyze the data. The analysis showed that the R2of the four models classify high in the category (R2 >0.70). Mature weight (A) of PO cattle predicted by Logistic (349 kg) and Gompertz (358 kg) were most appropriate. Out of the four models, the Logistic model was the most accurate in predicting the weight at puberty (174 kg) of PO cattle, but all observed cattle are still in the follicular phase.